Exploring determinant factors of differences between governmental accounting and national accounts budgetary balances in EU member-states - Jorge, S. M.; Jesus, M.; Laureano, R. M. S. (Transylvanian Review of Administrative Sciences, 2014)
Framed by the earnings management approach, this paper addresses the relationship between budgetary balances according to Governmental Accounting (GA) and National Accounts (NA), exploring factors that may explain both the materiality and diversity of the adjustments to be made when translating data from one into the other. Using data from Excessive Deficits Procedure reporting, embracing all EU member-States from 2007 to 2010, the analysis confirms that GA-NA adjustments reflect conceptual differences between the two systems, namely concerning recognition criteria. Regarding potential factors explaining adjustments, while none of the economic policy variables considered was found relevant in explaining either diversity or materiality, all technical accounting variables analyzed explained materiality, although only GA accounting basis explained diversity. As contributions to policy-making, this research shows that changing GA reporting basis into accruals reduces adjustments’ materiality and diversity. Therefore, in order to improve the quality of GFS, it is highly recommendable to achieve a GA system harmonized across Europe, such as IPSASs or EPSASs, allowing only very few options and imposing the accrual basis in both budgetary and financial systems. Also relevant is the need to strengthen the role of control and auditing in the GA reporting process, e.g. by Supreme Audit Institutions and external private firms, in order to avoid accounting discretion.